2010
DOI: 10.1089/aid.2009.0163
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses of HIV-Infected Children after Administration of Inactivated or Live Attenuated Influenza Vaccines

Abstract: Live-attenuated influenza vaccine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…pH1N1-Teff significantly decreased with high plasma HIV load, activated CD8+ T cells and regulatory B cells and moderately decreased with CD8+CD39+, CD4+TGFβ+ and CD4+IL10+ regulatory T cells. Both HIV infection and pregnancy increase the proportions of regulatory T cells[ 76 78 ], but regulatory T cells associated with HIV infection probably play the dominant role in attenuating Teff responses to IIV, since the decrease of Teff after influenza vaccination in previously primed non-pregnant HIV-infected individuals has been a recurrent and consistent observation in our studies [ 79 , 80 ]. CMI decreases were not observed in HIV-uninfected individuals after IIV3[ 81 ].…”
Section: Discussionsupporting
confidence: 76%
“…pH1N1-Teff significantly decreased with high plasma HIV load, activated CD8+ T cells and regulatory B cells and moderately decreased with CD8+CD39+, CD4+TGFβ+ and CD4+IL10+ regulatory T cells. Both HIV infection and pregnancy increase the proportions of regulatory T cells[ 76 78 ], but regulatory T cells associated with HIV infection probably play the dominant role in attenuating Teff responses to IIV, since the decrease of Teff after influenza vaccination in previously primed non-pregnant HIV-infected individuals has been a recurrent and consistent observation in our studies [ 79 , 80 ]. CMI decreases were not observed in HIV-uninfected individuals after IIV3[ 81 ].…”
Section: Discussionsupporting
confidence: 76%
“…Assays were performed using peripheral blood mononuclear cells (PBMCs) separated from blood shipped overnight. To differentiate CD4-from CD8-mediated responses, PBMCs were depleted of CD8+ cells using magnetic beads (Stem Cell Technologies) prior to stimulation for the ELISPOT assay, as previously described [29]. Results were expressed as spot-forming cells (SFCs) per 10 6 PBMCs.…”
Section: CMImentioning
confidence: 99%
“…To better understand the role of cell-mediated immunity, Adriana Weinberg from the University of Colorado compared ELISPOT responses to LAIV and TIV in HIV-infected children with respect to their CD4 T-cells, CD8 T-cells, and HIV viral loads. 88 This study found paradoxical decreases in influenza-specific CD8 T-cell mediated immune responses following TIV, whereas LAIV preserved such responses in HIVinfected children. No difference was noted in CD4 and HIV viral load after immunization in comparison to baseline.…”
Section: Other Respiratory Viral Infectionsmentioning
confidence: 56%
“…Myron Levin from The Children’s Hospital in Denver, Colorado showed that HIV‐infected children with CD4% ranging from 15 to ≥25 at the time of the study possessed similar serum hemagglutinin inhibition and neutralizing antibody responses as in HIV‐uninfected children following vaccination, indicating that these serologic responses are not affected. To better understand the role of cell‐mediated immunity, Adriana Weinberg from the University of Colorado compared ELISPOT responses to LAIV and TIV in HIV‐infected children with respect to their CD4 T‐cells, CD8 T‐cells, and HIV viral loads 88 . This study found paradoxical decreases in influenza‐specific CD8 T‐cell mediated immune responses following TIV, whereas LAIV preserved such responses in HIV‐infected children.…”
Section: Respiratory Virus Infections In the Immunocompromised Hostmentioning
confidence: 99%